(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Industrial training exposure allows the students to apply the theoretical knowledge gained in the classroom to real-world situations. This practical application enhances their understanding of concepts and fosters a deeper learning experience. Working in a real-world setting exposes students to various challenges and scenarios, helping them develop a wide range of practical skills. Objectives: (1) To identify the various challenges encountered by hotel management students during their industrial exposure training period. (2) To study about the impact of industrial exposure on the acquisition of practical skills, professional demeanor, and industry-specific knowledge among hotel management students. (3) To identify the facilities and support mechanisms offered by hotels to trainees during their industrial exposure is crucial for understanding the learning environment and ensuring a positive and enriching experience for the trainees. Methodology: The study is descriptive in nature. The sample for the study consists of 124 from Wayanad district, Kerala. The primary data required for the research was collected using a structured questionnaire which was distributed off-line. Stratified Random sampling technique was used for the study. Data was analyzed based on the category of the hotel where the training was done and the statistical analysis was based on percentage, chi square test, correlation analysis, ANOVA Test with the help of IBM SPSS Version 23. Results: 58.1% respondents agreed with the statement that they get benefited by doing the industrial exposure training; whereas, 17.7% strongly agreed, 13.7% of the respondents neither disagreed nor agreed, 8% disagreed and only a minority of 4% of the respondent said that they are not benefited by doing the industrial exposure training. The relationship between the category of the hotels and the stipend provided, weekly off and communication problems faced by the trainees had a statistically significant linear relationship (p<.001). Conclusion: The study suggests several measures for improvement, including providing accommodation, transportation support, stipends, uniforms, and compensation for extra work during peak hours. It also underscores the importance of addressing harassment issues and ensuring appropriate punishment for any misconduct. The research indicates challenges during industrial exposure training might lead to student discontinuation or a preference for higher studies after completing the course. This highlights the critical need for addressing these issues to retain and support students in their career journeys.